Evaluation of the biofilm-forming ability and molecular characterization of dairy Bacillus spp. isolates - Catania, Angela Maria; Di Ciccio, Pierluigi; Ferrocino, Ilario; Civera, Tiziana; Cannizzo, Francesca Tiziana; Dalmasso, Alessandra (Frontiers in Cellular and Infection Microbiology, 2023)
Food processing lines represents a suitable environment for bacterial biofilm formation. One of the most common biofilm-forming genera in dairy processing plants is Bacillus, which includes species that mayhave a negative impact on safety and/or quality of dairy products. In the current study, we evaluated the biofilm forming ability and molecular characteristics of dairy Bacillus spp. isolates (B. cereus and B. subtilis). Reference strains (B. cereus ATCC 14579 and B. subtilis NCTC 3610) were also included in theexperiment. All isolates were screened by micro-titer plate (96 wells) to assess their ability to form biofilm. Then, they were tested on two common food contact surfaces (polystyrene and stainless steel) by using 6-wellsplates and AISI 316stainless steel coupons. Biofilm formation, expressed as biofilm production index (BPI), was higher on polystyrene than stainless steel (except for B. cereus ATCC 14579). These observations were further confirmed by scanning electron microscopy, which allowed the examination of biofilm structure. Moreover, a possible correlation among total viable cell counts (CFU) and BPI was examined, as well as aconnection among biofilm formation and bacterial cell hydrophobicity.Finally, whole genome sequencing was performed highlighting a genetic similarity among the strains belonging to the same species. The presence of selected genes involved in biofilm formation was also examined showing that strains with a greater presence of these genes were able to produce more biofilms in the tested materials. Additionally, for B. cereusstrains enterotoxingenes were detected.